Two-photon imaging of hydrogen polysulfides in living cells and hippocampal tissues - Chung, Jeewon; Li, Haidong; Lim, Chang Su; Kim, Hwan Myung; Yoon, Juyoung (Sensors and Actuators, B: Chemical, 2020)
Hydrogen polysulfide (H2Sn) is an emerging topic of research because it plays a critical role in the pathological and physiological activities of an organism. Therefore, visual monitoring of H2Sn activity in living cells is critical. In our work, a two-photon fluorescent probe NI-H2S2 based on a naphthalimide skeleton was developed as a molecular tool for detecting hydrogen polysulfides in solution and live HeLa cells. NI-H2S2 showed rapid response and high sensitivity. Notably, hydrogen polysulfides in hippocampal tissue of mice could also be tracked using the probe under a two-photon fluorescence microscope. Therefore, this probe NI-H2S2 is expected to serve as a pragmatic tool for studying the physiological roles of hydrogen polysulfides in living cells and in vivo.
Keywords: Emerging topics; Fluorescent probes; High sensitivity; Physiological activity; Physiological roles; Two photon fluorescence; Two photon imaging; Visual monitoring; Cell imaging; Fluorescent probe; Hydrogen polysulfides; Two-photon